Will labour shortages and skills mismatches throw sand in the gears of the green transition in Belgium? - Mikkel Barslund; Wouter Gelade; Geoffrey Minne (National Bank of Belgium, 2024)
A significant reallocation of labour towards "green" jobs will be crucial for the transition to a decarbonised economy. Skills mismatches challenge the feasibility of this reallocation, particularly with many developed countries also facing substantial labour shortages. This paper analyses the factors that facilitate transitions into green shortage jobs in Belgium, with a particular emphasis on skills and the skill distance between workers' profiles and the skills required for these jobs. Our data combines longitudinal data of the labour force surveys, international classifications for green jobs, and regional classifications for shortage jobs. Half of green employment is in shortage occupations, underlining that this category may be pivotal both for economic development and for the achievement of climate objectives. Technical skills emerge as key across all education levels. Furthermore, we find that skills mismatches with respect to green shortage jobs are large, but the observed transitions to these jobs tend to involve less skill disruption than the green transition might require. Transitions from inactivity or unemployment to a green shortage job present even greater challenges and necessitate upskilling. Green shortage jobs are shown to differ significantly from other categories in terms of income, required skills, sector of activity, and training needs. Promoting labour mobility and vocational or on-the-job training is expected to yield substantial economic benefits in both the short and long term.
Keywords: J23; J24; J62; Q52; 330; Green jobs; Labour shortage; Skills; Occupational mobility